Detección Herpesvirus en Cassostrea gigas y C. angulata en Huelva.pdf - López Sanmartín, M.; Navas Triano, J.I. (AQUA 2012, 2012)
Herpesvirus infections have been related to mortalities of several species of cultured bivalve molluscs worldwide causing significant economic losses for aquaculture. Ostreid herpesvirus-1 (OsHV-1), assigned as a member of the Malacoherpesviridae family, has a particularly virulent genotype known as μvar. OsHV-1 μvar was first described in larvae and seeds of Crassostrea gigas affected by massive mortalities in France during 2008. Recently, OsHV-1 μvar infections have been associated with high mortality events involving the Pacific oyster in Europe, Australia and New Zealand. In order to assess the potential presence of OsHV-1, major natural beds of Crassostrea spp. in the Huelva coast were sampled in June-July 2011. Crassostrea species determination was performed by PCR-RFLP of the mitochondrial cytochrome oxidase C subunit I (COI) gene. OsHV-1 presence was investigated by PCR of the C region of virus genome using C2-C6 primers. OsHV-1 μvar was detected in C. gigas and Crassostrea angulata from natural beds without associated mortalities. OsHV-1 μvar was identified by PCR-RFLP analysis and DNA sequencing of PCR positive results. OsHV-1 infection was confirmed by in situ hybridization. Studies on genetic variability, distribution and prevalence of infection are currently underway. This study is funded by the projects HERPEMOL (JACUMAR) and BONAQUA (0433_BONAQUA_5_E POCTEP). Monserrat López Sanmartín has a phD grant from IFAPA supported by the European Union FEDER program. Financiado por el proyecto Bonaqua (0433_BONAQUA_5_E POCTEP) financiado por el FEDER (Fondo Europeo de Desarrollo Regional). www.juntadeandalucia.es/agriculturaypesca/ifapa/bonaqua . Las infecciones por herpesvirus se han relacionado con la mortalidad de varias especies de moluscos bivalvos cultivados en todo el mundo, causando significantes pérdidas económicas para la acuicultura. La variante herpesvirus-1 (OsHV-1), asignado como un miembro de la familia Malacoherpesviridae, tiene un genotipo conocido como OsHV-1 μvar, particularmente ...